1998
DOI: 10.1002/j.1550-8528.1998.tb00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Psychological Well‐Being, Quality of Life, and Health Practices in Moderately Overweight Women Participating in a 12‐Week Structured Weight Loss Program

Abstract: FREEDSON. Improved psychological well-being, quality of life, and health practices in moderately overweight women participating in a 12-week structured weight loss program. Obes Res. 1998;6:208-218. Objective: To study the effects of a 12-week weight loss strategy involving increased physical activity, self-selected hypocaloric diet, and group support on psychological wellbeing, quality of life, and health practices in moderately obese women. Methods; Eighty women aged 20--49 years weighing between 20-50% ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
119
0
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(136 citation statements)
references
References 38 publications
11
119
0
6
Order By: Relevance
“…13 The positive changes in mental HRQOL have been related to the magnitude of weight loss and the duration of follow-up, with some tendency for the scores to return towards baseline levels in subjects with less than a 20 kg weight loss at a 2 y followup. 18 The two previous randomised trials by Rippe et al 25 and Fontaine et al 26 showed improvement on mental health and vitality among obese women losing weight. In our study among men, there were transient improvements in the mental health scales of RAND-36 during treatment.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…13 The positive changes in mental HRQOL have been related to the magnitude of weight loss and the duration of follow-up, with some tendency for the scores to return towards baseline levels in subjects with less than a 20 kg weight loss at a 2 y followup. 18 The two previous randomised trials by Rippe et al 25 and Fontaine et al 26 showed improvement on mental health and vitality among obese women losing weight. In our study among men, there were transient improvements in the mental health scales of RAND-36 during treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Fontaine et al 26 had a 13-week trial comparing lifestyle physical activity with traditional aerobic physical activity showing improvement in physical functioning, physical role functioning, general health, vitality, social functioning and mental health, but no between-group differences in weight loss or HRQOL responses. Rippe et al 25 randomised 80 women into a 12-week weight loss group and a control group. The intervention group showed increased physical functioning, vitality and mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,19,26,31,39,51 Studies have investigated the association between PA and overall QoL, and the effects of PA on specifi c domains of QoL, 4,37 and it has often been reported an association with the "physical" and "mental" domains. 19,39,41,42,46,51 Evidence supports a positive association between PA and QoL, but the state of the art is not well established. The magnitude of this association is confl icting in different populations 4,37 and inconsistent results have been found when instruments for measuring PA and QoL, as well as designs, were compared.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] The previous weight loss studies with lifestyle intervention have shown various improvements in HRQL, but the studies have usually been very short in duration. [28][29][30][31] Studies with longer follow-up have shown a more modest improvement in HRQL, 32 and to our knowledge there are no reports of follow-up over 1 y.…”
Section: Introductionmentioning
confidence: 99%